Report of the Implementation of Work Package 6 "Implementation of Methodology" in the Framework of the IRNet Project - Smyrnova-Trybulska, Eugenia; Malach, Josef; Kostolanyova, K.; Morze, N.; Kommers, Piet; Noskova, T.; Pinto, P.; Delgado, S.; Drlik, Martin; Issa, Tomayess; Romanyukha, M. (Association for the Advancement of Computing in Education, 2017)
This article, prepared by an international team of researchers from different scientific areas connected with ICT, e-learning, pedagogy, and other related disciplines, focuses on the objectives and some results of the international project IRNet (www.irnet.us.edu.pl). In particular, the article describes research tools, methods, and a procedure of the Work Package 6 “Implementation of Methodology,” that is, objectives, tasks, deliverables, publications, and implementation of research trips in the context of the next stages and Work Packages of IRNet project – International Research Network.